DISTANCE PARENTING – IMPLICATIONS FOR SOCIAL WORK PRACTICE - Seepamore, Boitumelo Khothatso (Social Work/Maatskaplike Werk, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Many families in the Global South are inclined to split in order to survive the complex socio-economic conditions in which they find themselves. Labour migration is entrenched in South Africa and so is parenting from a distance. This paper contests the normalisation of split families and distance parenting, and considers the associated implications for children, their parents and substitute caregivers. It further discusses the persistence of stereotypical gender roles in parenting, even where both parents are absent from home. Finally, some recommendations are made for both practitioners and policy makers in relation to distance parenting